A quantitative method for blood lipoproteins using cellulose acetate electrophoresis - Magnani, H. N. (1971)
A rapid, inexpensive, and quantitative method is described for obtaining the levels of plasma very low, low, and high density lipoproteins using cellulose acetate electrophoresis and lipid assays without prior separation by ultracentrifuge or other techniques. It involves separation of the lipoproteins by cellulose acetate electrophoresis, followed by their identification with the ozone-Schiff reaction. The total lipoprotein concentration is estimated from the total plasma phospholipid, and the percentage of each component obtained by densitometric analysis of the stained electrophoretograms, using reflected light. For samples with a raised level of very low density lipoprotein, plasma triglyceride analysis is also required. The results obtained by the cellulose acetate electrophoresis method are in good agreement with those by the analytical ultracentrifuge and the preparative ultracentrifuge with refractometry. The theoretical assumptions on which the method is based have been shown to be valid.